2015
DOI: 10.1063/1.4928035
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the transmission phase of an electron in a quantum two-path interferometer

Abstract: A quantum two-path interferometer allows for direct measurement of the transmission phase shift of an electron, providing useful information on coherent scattering problems. In mesoscopic systems, however, the two-path interference is easily smeared by contributions from other paths, and this makes it difficult to observe the true transmission phase shift. To eliminate this problem, multi-terminal Aharonov-Bohm (AB) interferometers have been used to derive the phase shift by assuming that the relative phase sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…However, the main focus was in the opening of the systems and in partial coherent transport using one-dimensional models for the leads without taking into account other distorting effects like possible scattering in the junctions of the interferometric arms. Experimental advances in this direction have been made recently trying to find more clear criteria about when the phase measurements can be trusted and when the contributions from multiple path can be neglected [33]. A different approach was taken by Fischer et al [34].…”
Section: Introductionmentioning
confidence: 99%
“…However, the main focus was in the opening of the systems and in partial coherent transport using one-dimensional models for the leads without taking into account other distorting effects like possible scattering in the junctions of the interferometric arms. Experimental advances in this direction have been made recently trying to find more clear criteria about when the phase measurements can be trusted and when the contributions from multiple path can be neglected [33]. A different approach was taken by Fischer et al [34].…”
Section: Introductionmentioning
confidence: 99%
“…The measured phase shift can be unintentionally modified from the true phase shift by contributions from multi-path interferences [18,19]. Recently we have demonstrated a way how to measure the true transmission phase of an electron [20]. We have shown that the criterion used in our experiments using our original two-path interferometer ensures the proper measurement [20] while those used in other previous experiments are a bit less reliable [1,3].…”
mentioning
confidence: 89%
“…Recently we have demonstrated a way how to measure the true transmission phase of an electron [20]. We have shown that the criterion used in our experiments using our original two-path interferometer ensures the proper measurement [20] while those used in other previous experiments are a bit less reliable [1,3]. Therefore a careful experimental investigation of is required to have comprehensive understanding of the phase behavior across a QD.Here we investigate the transmission phase across a QD around the crossover between single-level and multi-arXiv:1709.08876v1 [cond-mat.mes-hall]…”
mentioning
confidence: 99%
“…We focus this study on the tunneling wire "flying qubit" geometry sketched in Fig. 1a and studied experimentally in 10,11,26,27 . The device consists of two quasione dimensional wires labeled ↑ (upper) and ↓ (lower) connected to four electrodes: two on the left L↑, L↓ and two on the right R↑, R↓.…”
Section: A Two Paths Electronic Interferometer Using a Split Wirementioning
confidence: 99%